THE IMPACT OF EDUTAINMENT TECHNOLOGIES ON STUDENTS’ MOTIVATION - Charos Adilova (European Science Publishing, 2025)
Edutainment technologies, a blend of education and entertainment, have emerged as a powerful tool in modern education. This study explores their influence on students’ motivation, focusing on the ways these technologies engage learners and enhance their academic experience. By incorporating interactive elements such as gamification, simulations, and multimedia content, edutainment tools foster an engaging learning environment that appeals to various learning styles. Research indicates that edutainment technologies improve knowledge retention and critical thinking skills by making learning enjoyable and relatable. Additionally, these tools promote active participation, collaboration, and problem-solving among students. They also address the motivational challenges often encountered in traditional teaching methods by providing immediate feedback and rewarding achievements, which keep learners motivated. However, this approach is not without challenges. Effective integration requires careful alignment with curriculum goals and consideration of students’ needs. Moreover, over-reliance on entertainment may detract from the educational value if not implemented thoughtfully.In conclusion, edutainment technologies significantly impact students’ motivation by making learning more dynamic and accessible. Further studies are necessary to optimize their integration into educational practices while addressing potential drawbacks.
Keywords: Edutainment technologies, students’ motivation, gamification, interactive learning, multimedia content, knowledge retention, critical thinking, active participation, educational engagement, curriculum integration.